Experimental study of a multi-stage evaporative cooler (University of Thi-Qar Journal for Engineering Sciences, 2016)
In this study, the evaporative cooler is developed by adding multistage of heat exchangers (air – air and water – air) to cool indirectly and indirectly the input air and then cooling directly inside the classical evaporative cooler. The multistage evaporative cooler is assisted to reduce the energy consumption, environmental pollution, global warming phenomenon and manufacturing cost compared than compression refrigeration systems. The multistage evaporative cooler is suitable and done in houses and large buildings with relatively high temperatures and humidity. The experimental results of developed evaporative cooler showed that adding cooling stage to classical cooler reduces the out dry bulb temperature about (50%) and the specific humidity by (70%)